2000
DOI: 10.1073/pnas.080078197
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of vaccinia virus protein–protein interactions

Abstract: To detect interactions between proteins of vaccinia virus, we carried out a comprehensive two-hybrid analysis to assay every pairwise combination. We constructed an array of yeast transformants that contained each of the 266 predicted viral ORFs as Gal4 activation domain hybrid proteins. The array was individually mated to transformants containing each ORF as a Gal4 -DNAbinding domain hybrid, and diploids expressing the two-hybrid reporter gene were identified. Of the Ϸ70,000 combinations, we found 37 protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
211
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(222 citation statements)
references
References 57 publications
11
211
0
Order By: Relevance
“…Therefore, we can expect that the future accumulation of more interaction data will enable us to predict protein function more precisely. In addition, we will soon be able to apply our method to the proteins of other organisms, because several projects to determine protein-protein interaction data of various organisms are ongoing (Walhout et al, 2000;McCraith et al, 2000). The third column represents the frequency of proteins belonging to each class and the subsequent columns represent the percentage prediction accuracy for each n value (the dummy prediction accuracy obtained from randomized function assignments is shown in parentheses).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we can expect that the future accumulation of more interaction data will enable us to predict protein function more precisely. In addition, we will soon be able to apply our method to the proteins of other organisms, because several projects to determine protein-protein interaction data of various organisms are ongoing (Walhout et al, 2000;McCraith et al, 2000). The third column represents the frequency of proteins belonging to each class and the subsequent columns represent the percentage prediction accuracy for each n value (the dummy prediction accuracy obtained from randomized function assignments is shown in parentheses).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, considering that 35 different ORFs were recognized and that a total of 258 potential ORFs were studied, it can be concluded that class I restricted responses can recognize at least 13.6% of the proteins encoded by the vaccinia virus genome. The 35 ORFs recognized were analyzed with respect to stage of expression (early͞intermediate vs. late) (21,(25)(26)(27)(28)(29) and function (structural protein, virulence factor, and regulation). We also analyzed the percent homology of the vaccinia epitopes with the comparable peptides in the genomes of variola major and MVA (Tables 8 and 9; see also Table 18, which is published as supporting information on the PNAS web site).…”
Section: Structural Analysis Of the Antigens Recognized After Vaccinamentioning
confidence: 99%
“…Protein-protein interaction maps have been studied, at different levels, in a variety of organisms including viruses (Bartel et al, 1996;Flajolet et al, 2000;McCraith et al, 2000), prokaryotes (Rain et al, 2001), yeast (Ito et al, 2000), and multicellular organisms such as C. elegans (Walhout et al, 2000). Previous studies have mainly used the so called two-hybrid assay (FromontRacine et al, 1997), based on the properties of sitespecific transcriptional activators.…”
Section: Topological Properties Of Real Proteome Mapsmentioning
confidence: 99%